2021
DOI: 10.1002/srin.202000650
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging Treatment on Precipitates and Intrinsic Mechanical Behavior of Austenitic Matrix in Ti–V–Nb‐Alloyed High‐Manganese Steel

Abstract: The collaboration of precipitated particles and austenitic matrix plays a significant role in the overall wear performance of high‐manganese (high‐Mn) austenitic steels. The austenitic matrix cannot support micrometer‐sized precipitates because of its poor Young's modulus and hardness before work hardening, and the relative sliding of abrasive particles over the matrix may result in the precipitates detaching from the matrix and deteriorating the overall wear performance of the steels. Herein, a solid‐solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…[7,8] Vanadium (V) is particularly attractive. [9][10][11][12][13][14] Although aging at temperatures in the range of 673 to 773 K (400 to 500 °C) has been proposed for a 0.6C-17Mn-0.45 V (in wt pct), grade [13,14] precipitation is possible at higher temperatures. [10] Higher temperature aging is more desirable due to the ability to avoid harmful carbide formation and to potentially achieve shorter treatment times but the extent to which the favorable nanoscale precipitates, such as those reported in references, [13,14] form at higher temperatures is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] Vanadium (V) is particularly attractive. [9][10][11][12][13][14] Although aging at temperatures in the range of 673 to 773 K (400 to 500 °C) has been proposed for a 0.6C-17Mn-0.45 V (in wt pct), grade [13,14] precipitation is possible at higher temperatures. [10] Higher temperature aging is more desirable due to the ability to avoid harmful carbide formation and to potentially achieve shorter treatment times but the extent to which the favorable nanoscale precipitates, such as those reported in references, [13,14] form at higher temperatures is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al have found that second-phase particles with different volume fractions, sizes, and shapes were precipitated from Ti-V-Nb alloyed high manganese steels by aging the steels at 400°C/1h, 450°C/1h, and 500°C/1h, respectively. The density and homogeneity of the submicron precipitates increased with a rise in aging temperature [25]. Guofeng Zhangdeng et al have reported high strength and ductility of Fe-Mn-Al-C austenitic steels achieved by vanadium microalloying and aging, due to the synergistic effect of double nanoparticle precipitation consisting of nanoscale VC and κ-carbide particles [26].…”
Section: Introductionmentioning
confidence: 99%